Application Of The Seven-Box Organizational Diagnosis Model Preziotion To Develop The Organization At PT. Manggala Site Muara Enim - Ilpiyanto, Marko; Wibowo , Wahyu (Journal of Management, Economic, and Accounting, 2024)
PT Manggala is a mining service provider company operating in South Sumatra and East Kalimantan which are the two provinces that have the largest coal reserves in Indonesia. The large number of mining service provider companies has made competition as a mining service provider increasingly stringent. Therefore the author raises a research topic entitled "Application of the Seven- Box Preziosi Organizational Diagnostic Model to Develop the Organization of PT Manggala Site Muara Enim". The application of Preziosi's Seven-Box Organizational Diagnostic Model is a development of the Six-Box Weisbord Model (1976) with six variables namely Purpose, Structure, Relationship, Rewards, Leadership and Helpful Mechanism, each of which is divided into ten research indicators. Then added the seventh variable developed by Preziosi (1980), namely Attitude Toward Change which is divided into five indicators so that the total indicators in this study are sixty five. The results showed that the average achievement value of the Purpose Variable was 77%, Structure Variable was 72%, the Relationship Variable was 77%, the Reward Variable was 65.7%, the Leadership Variable was 74.7%, Helpful Mechanism Variable was 66.9%, and the Attitude Toward Change variable by 74%. All of the variable values need to be increased again by the company in order to improve the company's performance in order to maintain the company's competitive value as a provider of mining services, especially at the Muara Enim Site.